IMPLEMENTASI PENDEKATAN STEAM (SCIENCE, TECHNOLOGY, ENGINEERING, ART, MATHEMATICS) DI KELAS VA SDN 131/IV KOTA JAMBI - Rozi, M. Fattur; Ahmad Hariandi; Andi Gusmaulia Eka Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of the STEAM (Science, Technology, Engineering, Art, Mathematics) approach in the learning process of Class Va at SDN 131/IV Kota Jambi. The STEAM approach is an educational innovation that integrates five disciplines to foster students' critical thinking, creativity, and collaboration skills. This research explores how teachers apply the STEAM approach in learning activities, the types of activities used, as well as students' responses and engagement during the process. A qualitative descriptive method was employed, with data collected through observation, interviews, and documentation. The findings of this study are expected to provide a clear picture of the effectiveness and challenges in implementing the STEAM approach in elementary schools and serve as a reference for developing innovative and contextual learning strategies.